A Reference Finding Rarely Seen in Primary Hyperparathyroidism: Brown Tumor - F. Mantar; S. Gunduz; U. R. Gunduz (Case Reports in Medicine)
Primary hyperparathyroidism is an endocrinopathy which is characterized with the hypersecretion of parathormone. During the progress of the disease bone loss takes place due to resorption on the subperiosteal and endosteal surfaces. Brown tumor is a localized form of osteitis fibrosa cystica, being part of the hyperparathyroid bone disease. It is rarely the first symptom of hyperparathyroidism. Nowadays, the diagnosis is made at an asymptomatic or minimally symptomatic stage. We present a male patient presented with a massive painless swelling in the left maxilla as the first manifestation of primary hyperparathyroidism due to a parathyroid adenoma. Parathyroidectomy was performed, and there was a regression of the bone lesion, without the need of performing other local surgical procedures.